Road Maintenance Management Using Pavement Condition Index (PCI) Survey - Sita, Tisara (ReTII, 2018)
Road maintenance management is a very important issue in the highway management. Existing roads infrastructure on Jl. Prof. Dr. Sardjito and Jl. AM. Sangaji that has been passed by the volume of traffic requires maintenance to prevent severe condition as predicted in design life. Therefore, the objective of this study is to appraise a survey pavement condition method so that the road can be functional more optimal. This study was visually completed by using Pavement Condition Index (PCI) method. It was started by dividing the road into several units length in 30 m for each unit sample. Then, each of the sample unit was observed, evaluate, and analyze to identify the distress type and severity level in order to obtain PCI rating value of the pavement condition. The result of the study showed that the distress types in this research included the corrugation, longitudinal and transverse cracking, patching, polished aggregate, raveling, and potholes. The most distresses that usually occur are longitudinal and transverse cracking, patching and raveling with low severity. From the analysis of PCI method, the rating for both road conditions is excellent; therefore, the suggestion that can be given for those sample roads is preventive maintenance to extend a pavement's life. The road repair options are compared between PCI method by US Army and Asphalt Institute.